Wireless security assessment on the FTMSK2 building / Zainurzaman Mah Sangit @ Kasmat - Mah Sangit @ Kasmat, Zainurzaman (2007)
Many university information services departments have been gradually extending their wireless local area network (WLAN) coverage in order to provide wireless access to students, staff, and faculty throughout their campuses. There is a growing concern about security risks inherent with a wireless data network, such as loss of confidentiality, loss of integrity and loss of network availability. Numerous flaws have been discovered in WEP, and studies have shown that many wireless LANs are installed with their default settings. This thesis explores security vulnerabilities in Wireless-Fidelity (Wi-Fi) networks. A thorough description about WLAN and critical security holes is briefly described. First a guide to the necessary equipment and how to set it up as an attack platform is provided. Tools and techniques for measuring IEEE 802.11 WLANs also included giving the reader a greater insight into how computer systems are utilized by hackers, and eventually enable the design of more secure systems. The tools are all open-source software available for download and the techniques all use open-source software and off-the-shelf hardware components. Later it is demonstrated the tools’ utility in monitoring traffic at FTMSK2 building and show how the lack of security may aid a malicious hacker to exploit interesting targets beyond the realm of Wi-Fi. Our tool captures only packets of interest for optional storage and further analysis, thus greatly reducing resource requirements. The preliminary results obtained from these measurements are presented.